The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/fwb.12943
|View full text |Cite
|
Sign up to set email alerts
|

Biotic resistance by snails and fish to an exotic invasive aquatic plant

Abstract: Hydrilla verticillata (Hydrocharitaceae) is an exotic invasive macrophyte that has caused severe ecological and economic damage worldwide. H. verticillata has invaded the main channel of the river in the Upper Paraná River floodplain (Brazil), but it has not become established in floodplain lakes. Although some abiotic factors have been shown to affect the success of H. verticillata invasions, the role of biotic interactions remains unclear. Here, we set a laboratory experiment investigating how interactions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…We therefore reject our second hypothesis, as we did not find selective feeding by the herbivore on the invader. This contradicts findings of previous studies, which have shown herbivory to reduce success of invasion of alien species (Parker et al, 2007;Ribas et al, 2017). Alternatively, the success of highly invasive aliens is often attributed to a release from their natural enemies (Enemy Release Hypothesis; Keane & Crawley, 2002), but these benefits could be lost over time since introduced species can acquire new enemies, depending on how long the invader has been present in the introduced range (residence time; Schultheis, Berardi, & Lau, 2015).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We therefore reject our second hypothesis, as we did not find selective feeding by the herbivore on the invader. This contradicts findings of previous studies, which have shown herbivory to reduce success of invasion of alien species (Parker et al, 2007;Ribas et al, 2017). Alternatively, the success of highly invasive aliens is often attributed to a release from their natural enemies (Enemy Release Hypothesis; Keane & Crawley, 2002), but these benefits could be lost over time since introduced species can acquire new enemies, depending on how long the invader has been present in the introduced range (residence time; Schultheis, Berardi, & Lau, 2015).…”
Section: Discussionmentioning
confidence: 71%
“…Herbivores foraging on native plant species can also reduce native plant competition abilities (Le Bagousse-Pinguet, Gross, & Straile, 2012; Li, Xiao, Zhang, & Dong, 2013). Furthermore, herbivores can also indirectly affect alien plant establishment through non-trophic effects, including alteration of disturbance regimes and/or resource availability, for example by increasing nutrient recycling (Ribas et al, 2017). The impact of herbivores on alien plant invasions therefore varies by their feeding preferences, and how they may otherwise interact with species in the food web.…”
Section: Introductionmentioning
confidence: 99%
“…If temporal covariance between species richness and biomass is positive and increases both for non-native and native assemblages, the establishment of newly introduced species apparently occurs without "invasion resistance" (Lyons and Schwartz 2001). Native assemblages with higher species richness at the beginning of the time series can resist the colonisation of non-native propagules (Ribas et al 2017). However, successful invaders are relatively different, considering native functional traits (Skóra et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the upper Paraná River basin, the population size of H. verticillata has increased (Sousa 2011), but this invasive species has not become established in the river's floodplain lakes. One of the main reasons for the failure of H. verticillata colonization in this area is likely the high concentration of organic matter in the lake sediments (Silveira and Thomaz 2015); however, P. canaliculata does inhabit these lakes, and could be controlling the population size of H. verticillata (Ribas et al 2017), since snail herbivory is reported to control aquatic macrophyte populations (e.g., Sheldon 1987;Pieczynska 2003;Carlsson and Lacousière 2005;Xiong et al 2008;Li et al 2009). Indeed, H. verticillata has started to colonize these lakes, but only a few young plants have been observed, and they never reach maturity (M.S.D.-F., unpublished data 2017).…”
Section: R a F Tmentioning
confidence: 99%
“…2017). A previous experiment has provided evidence that this snail, along with herbivorous and shredder fish, has the potential to increase resistance against H. verticillata invasion (Ribas et al 2017); however, the mechanisms that explain herbivory (e.g., plant palatability) are less well understood.…”
mentioning
confidence: 99%